2016
DOI: 10.1002/pip.2790
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive simulation study of industrially relevant silicon solar cell architectures for an optimal material parameter choice

Abstract: Solar cell production always requires a tradeoff between cell efficiency and production costs. This also concerns the choice of the silicon base material. In general, a long base lifetime is beneficial to achieve high conversion efficiency, but it strongly depends on the cell concept to which extent the cell performance is improved and whether a payback of the higher material costs can be expected. Therefore, in this comprehensive simulation study of various industrially relevant solar cell architectures, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Rather similar conclusions were also drawn for the thickness variation. Such recombination‐induced effects on FF were already reported, for instance, for impurity recombination within the silicon bulk, for injection‐dependent surface recombination, or recombination in the (dark) perimeter of this small‐area solar cells embedded in a 4‐inch wafer …”
Section: Solar Cell Results and Previous Analysissupporting
confidence: 66%
See 2 more Smart Citations
“…Rather similar conclusions were also drawn for the thickness variation. Such recombination‐induced effects on FF were already reported, for instance, for impurity recombination within the silicon bulk, for injection‐dependent surface recombination, or recombination in the (dark) perimeter of this small‐area solar cells embedded in a 4‐inch wafer …”
Section: Solar Cell Results and Previous Analysissupporting
confidence: 66%
“…Although peak efficiency values in the range of 25% were observed for all studied variations, the I‐V parameters revealed significant trends as a function of W and ρ b (compare experimental data shown in Figure ). For instance, the efficiency was found to decrease with increasing resistivity, which was not expected as rather ρ b ‐independent efficiencies have been predicted . The observed efficiency reduction was found to correlate with an FF reduction, which is not caused by the series resistance of the cells or the parallel (shunt) resistance.…”
Section: Solar Cell Results and Previous Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Many of these advanced device concepts have two-or threedimensional architectures. We used device models with effective simulation parameters [15] in order to resemble the performance of these advanced concepts. Figure 2 shows the simulated module efficiencies depending on the Si wafer thickness.…”
Section: Pv Device Simulation: Effect Of Wafer Thickness On Efficiencymentioning
confidence: 99%
“…The lifetime distribution, the resistivity and the dislocation density for mc-Si are the key parameters that are used to predict the solar cell performances. A high resistivity was shown to improve the cell performances for most cell architectures, except for some PERC designs where 3D carrier transport was happening [5]. Yet another study has shown that these results are to be considered cautiously as the lifetime limiting impurities present in the material have a great influence on the dependence of the cell efficiency with the resistivity [6].…”
Section: Introductionmentioning
confidence: 99%